Penerapan Model Pembelajaran Self Organized Learning Environments (SOLE) pada Kegiatan Pembelajaran Daring untuk Meningkatkan Hasil Belajar (Studi Kasus pada Mata Pelajaran Desain Grafis Percetakan Kelas XI Multimedia SMK Negeri 5 Malang) - Zaky Nur Abyan; Satrio Hadi Wijoyo; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
One of the characteristics of the application of the SOLE model is the use of internet access during the learning process so that it can make it easier for students to learn online. The SOLE learning model was chosen because it is in accordance with the current state of students who do not take part in face-to-face learning due to the impact of the pandemic, which makes learning activities carried out online. The SOLE learning model is an independent learning process by utilizing the internet and smartphones owned by students. To be able to find out student learning outcomes in printing graphic design subjects, research was carried out using the Self Organized Learning Environment (SOLE) learning model. The development of learning methods is used as a means to facilitate the learning process. One of the most frequently used supports for the learning process is a smartphone. During the pandemic, the learning process in schools is done online. Learning is not done face-to-face directly but by utilizing applications and smartphones for the learning process. The learning system uses classroom applications with power point materials and assigns assignments to students. In the online learning process, the problem that occurs is that the teacher cannot find out student learning outcomes about the printed graphic design lessons given because during the pandemic students are not enthusiastic if only given material with the lecture method. In the application of the SOLE learning model there is an influence on student learning outcomes.